Rainer Maria Rilke and Jugendstil Affinities, Influences, Adaptations - Webb, Karl Eugene (UNC Studies in the Germanic Languages and Literatures, 1978)
This study focuses on the striking relationship between one of the most important and enigmatic poets of the twentieth century and the art and artists of the Art Nouveau. The author explores the depth of the relationship itself, examines Rilke's activities as an art critic, and analyzes the profound influence of Art Nouveau upon the themes, motifs, and structure of the poet's early works.